2013
DOI: 10.1002/rnc.2972
|View full text |Cite
|
Sign up to set email alerts
|

Robust adaptive control for a class of cascaded nonlinear systems with applications to space interception

Abstract: SUMMARYThis paper proposes a robust H ∞ ‐based adaptive backstepping control scheme for the output stabilization of a special class of cascaded nonlinear systems. This kind of systems possess the feature that the first sub‐equation is a linear perturbed system, whereas the rest ones perform a general semi‐strict feedback form. Different from the conventional backstepping design approach, the special cascaded structure ensures to introduce the H ∞  technique to the backstepping procedure such that both the robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 52 publications
(97 reference statements)
0
14
0
Order By: Relevance
“…Remark To ensure that the mass estimate truem^ch stays in a closed domain, the common projection function is defined as follows: projtruem^chfalse(normalΦfalse)= {array0arrayifm^chmmaxandΦ>0array0arrayifm^chmminandΦ<0arrayΦarrayotherwise. Obviously, the projection function has the jump discontinuity at the points truem^ch=mmax and truem^ch=mmin. On the contrary, the proposed projection function is continuous and has the nice properties (Equation ); we can guarantee that if we choose the initial mass guess truem^chfalse(0false) inside the set normalΩmch, the mass estimate truem^chfalse(tfalse) can always stay inside the set trueΩ^truem^ch.…”
Section: Adaptive Sliding‐mode Control Law Designmentioning
confidence: 99%
See 3 more Smart Citations
“…Remark To ensure that the mass estimate truem^ch stays in a closed domain, the common projection function is defined as follows: projtruem^chfalse(normalΦfalse)= {array0arrayifm^chmmaxandΦ>0array0arrayifm^chmminandΦ<0arrayΦarrayotherwise. Obviously, the projection function has the jump discontinuity at the points truem^ch=mmax and truem^ch=mmin. On the contrary, the proposed projection function is continuous and has the nice properties (Equation ); we can guarantee that if we choose the initial mass guess truem^chfalse(0false) inside the set normalΩmch, the mass estimate truem^chfalse(tfalse) can always stay inside the set trueΩ^truem^ch.…”
Section: Adaptive Sliding‐mode Control Law Designmentioning
confidence: 99%
“…where > 0 and Φ = s T B (q) . Define the setΩm ch = {m ch ∶ m min − ≤m ch ≤ m max + }; it can be easily concluded that the projection-based adaptive law (27) has the following nice properties:…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…While usually dependent on some structural properties of the system, adaptive control is valuable because of its ability to solve tracking problems for a wide range of possible values of the unknown model parameters including higher‐order systems. One area where adaptive control is important is in aerospace problems . In basic adaptive control for some classes of control systems (such as linear systems), one can often use nonstrict (or weak) Lyapunov functions to ensure that tracking objectives are realized, and then achieve parameter identification (ie, convergence of the parameter estimates to the true parameter values) provided that a persistency of excitation (PE) condition is also satisfied.…”
Section: Introductionmentioning
confidence: 99%